Pancreas transplantation - Chaib, Eleazar; Meirelles Junior, Roberto Ferreira; Santos, Vinicius Rocha; Bacchella, Telesforo; D'Albuquerque, Luiz Augusto Carneiro (Revista de Medicina, 2009)
Insulin-dependent diabetes mellitus is associated with a high incidence of management problems and secondary complications. Clinical pancreas transplantation began at the University of Minnesota in 1966, initially with a high failure rate, but the outcome improved in parallel with other organ transplants. The authors retrospectively analyzed the factors associated with the increase success rate of pancreas transplants, among them donor selection, technical aspects of the retrieval of the pancreas, recipient operation with bladder drainage and Roux-en–Y for drainage of the exocrine pancreatic secretion, immunosupression protocol, technical failures such as vascular thrombosis, hemorrhages, rejection and infection at Hospital das Clinicas from University of Sao Paulo School of Medicine. Graft and patient survival rate is also described from 1997 to 2006.